Musyawarah Sebagai Landasan Demokrasi Dalam Pemikiran Islam - yusron kamil, yusron; Rini Ojtaviani; sukron; M. Fadhil Seprinaldi (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
Deliberation and democracy are two things that cannot be separated, because deliberation is the foundation of democracy itself. Without deliberation, a country that upholds democratic values ​​will not function. As stated in the Koran and also the fourth principle of Indonesia's foundation, namely Pancasila. In the deliberation process, dialogue occurs between one and another without making decisions personally, the voice of the people is also included, resulting in joint decisions, not individualistic ones. As exemplified by the Prophet Muhammad SAW, he was not rash in making decisions, but he always invited his friends to deliberation and consensus to listen to suggestions and input from his friends, so as to produce joint decisions, not rash and individual. As with democracy, in the election of people's representatives a general election is held so that a joint decision is made. Democracy is a system of government while deliberation is a working system in it. Therefore, we need to know that deliberation and democracy cannot be separated because they are interrelated. Keyword: Democracy; Deliberation; Islamic Thought